Balance and management of CRS and infection following CD19-targeted CAR T-cell therapy in primary refractory high-grade B-cell lymphoma: a case report - Lu, Nannan; Zhang, Yajing; Wang, Chunmeng; Yang, Qingming; Rong, Guanghua; Liu, Yang; Han, Weidong (Frontiers in Hematology, 2025)
BackgroundCD19-targeted chimeric antigen receptor T (CAR T) cell therapy has revolutionized the treatment of refractory/relapsed B-cell malignancies. However, this therapy introduces significant safety concerns, including cytokine release syndrome (CRS) and infections, both of which can lead to life-threatening complications. These two complications often require conflicting treatment approaches, making it challenging to balance patient safety and therapeutic effectiveness. The optimal approach to managing infections complicated by CRS remains unclear.Case presentationA 54-year-old man with primary refractory high-grade B-cell lymphoma, who had failed multiple prior therapies, received CD19 CAR T-cell therapy after bridging therapy and intensive lymphodepletion. He developed a severe diffuse alveolar hemorrhage induced by CRS complicated with virus infection following CAR T-cell infusion. Despite aggressive therapeutic approaches including anti-infection measures, immune modulation, and anticytokine agents, no significant clinical improvement was initially observed. The patient’s toxicity was effectively managed, ultimately leading to a complete response (CR), only after the introduction of glucocorticoids following the median time to peak CAR T-cell expansion. The patient sustained this CR for over 36 months, until January 2025.ConclusionThis case highlights the importance of early diagnosis and management of CRS and infection after CAR T-cell therapy, offering critical insights into managing adverse reactions and optimizing patient outcomes.